Bone disease after jejuno-ileal bypass for morbid obesity. Issue 691 (May 1983) - Gilmore, I. T.; Eastwood, J. B.; Ellis, W. R.; Luck, V. A.; Fenton, S.; O'Grady, A. J.; Harris, E.; Murray-Lyon, I. M.
Abstract : Fifteen patients who had undergone a 14 inches X 4 inches jejuno-ileal bypass operation for obesity, 3 to 4 years earlier, were investigated by iliac bone biopsy, radiology and routine biochemistry, including 25-hydroxy-vitamin D and parathyroid hormone estimations. Two patients had histological osteomalacia which was mild in one. A further 9 patients had abnormal bone biopsies, there being an excess of trabecular bone surface covered by osteoid with a normal or reduced amount of calcification front. Six of these 9 showed an increase in trabecular resorption, although in none were there excessive numbers of osteoclasts. The likely explanation for these findings is that these 9 patients had early osteomalacia with mild hyperparathyroidism, making a total of 11 patients out of 15 with osteomalacia. Radiology and blood chemistry were poor predictors of histological bone disease.